2020
DOI: 10.1186/s13002-020-00390-4
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge about sustainable harvesting and availability of wild medicinal plant species in Lemnos island, Greece

Abstract: Background: In Europe and the Mediterranean, over-exploitation and destructive harvesting techniques have been identified as two critical threats affecting the sustainable harvesting of wild medicinal plant (WMP) species. However, unsustainable harvesting is not an issue everywhere and localized assessments are needed. Local knowledge has been praised for its potential for local short-term assessments. In this study, we aimed to register the known, harvested, and locally utilized WMP species and understand loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 64 publications
(111 reference statements)
1
32
1
Order By: Relevance
“…The plant part used and exploitation method can effect on medicinal species loss. Harvesting of plant seed and whole of aerial parts endangered sustainable use of medicinal plants 41 , 52 . The ecological importance of B. persicum as one of the medicinal plants with the highest CV, has declined 80% and 60% in the both pastoral rangelands, due to over-collecting of its seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The plant part used and exploitation method can effect on medicinal species loss. Harvesting of plant seed and whole of aerial parts endangered sustainable use of medicinal plants 41 , 52 . The ecological importance of B. persicum as one of the medicinal plants with the highest CV, has declined 80% and 60% in the both pastoral rangelands, due to over-collecting of its seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Plants that have been recorded in previous ethnobotanical studies in Turkey and other Balkan and Mediterranean countries are also presented in Table 1, Table 2 (Agelet and Vallès, 2003;Akerreta et al, 2007a;Akerreta et al, 2007b;Axiotis et al, 2018;Bellia and Pieroni, 2015;Benítez et al, 2010;Benítez et al, 2012;Calvo and Cavero, 2014;Calvo et al, 2011;Camejo-Rodrigues et al, 2003;Carrió and Vallès, 2012;Cavero et al, 2011a;Cavero et al, 2011b;Cornara et al, 2009;De Natale and Pollio, 2007;González et al, 2010;Gras et al, 2019;Guarrera et al, 2005;Łuczaj et al, 2019;Matejic et al, 2020;Mattalia et al, 2020a;Mattalia et al, 2020b;Mattalia et al, 2020c;Mautone et al, 2019;Menale and Muoio, 2014;Mustafa et al, 2012;Mustafa et al, 2015;Mustafa et al, 2020;Novais et al, 2004, Papageorgiou et al, 2020Parada et al, 2009;Petrakou et al, 2020;Pieroni, 2000;Pieroni et al, 2002;Pieroni, 2017;Rigat et al, 2007;Rigat et al, 2013;Sansan...…”
Section: Local Namementioning
confidence: 99%
“…The list of medicinal taxa used -131 species -is not very long, taking into consideration the fact that it is spread over a few hundred kilometers and divided into islands with different histories. For comparison, Papageorgiou et al (2020) recorded the harvesting of 144 species of medicinal plants just on one island (Lemnos) in Greece, and Axiotis et al (2018) found 109 species of medicinal importance on only nine east Egean islands. Vitasović-Kosić et al (2017) found 90 species used inĆićarija, a small part of Istria in mainland Croatia, and Varga et al (2019) found 83 species of medicinal plants used in a small region of inland Dalmatia.…”
Section: Comparison With Other Areasmentioning
confidence: 99%
“…They are however counterbalanced by those who try to document the ethnomedical knowledge for reasons other than only finding new medicinal species. For example, the use of medicinal plants is entwined with issues such as the protection of rare plants and their overharvesting (Barata et al, 2016;Grigoriadou et al, 2020;Papageorgiou et al, 2020). The cultural aspects of healing with the use of herbs are also important and have been summarized by Quave et al (2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation